Clinical neurovirology - Nath, Avindra; Berger, Joseph R., 1951- (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
"This second edition includes the basic science, clinical features, imaging, pathology and treatment of specific viral entities affecting the CNS. It will assist professionals in their attempt to identify, examine and manage viral CNS infections and unravel the therapeutic and diagnostic challenges associated with viral CNS disorders"--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Central Nervous System Viral Diseases; DNA Virus Infections; Retroviridae Infections; RNA Virus Infections